2016
DOI: 10.1038/ncomms13443
|View full text |Cite
|
Sign up to set email alerts
|

An immunostimulatory dual-functional nanocarrier that improves cancer immunochemotherapy

Abstract: Immunochemotherapy combines a chemotherapeutic agent with an immune-modulating agent and represents an attractive approach to improve cancer therapy. However, the success of immunochemotherapy is hampered by the lack of a strategy to effectively co-deliver the two therapeutics to the tumours. Here we report the development of a dual-functional, immunostimulatory nanomicellar carrier that is based on a prodrug conjugate of PEG with NLG919, an indoleamine 2,3-dioxygenase (IDO) inhibitor currently used for revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
139
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(145 citation statements)
references
References 36 publications
5
139
1
Order By: Relevance
“…These multifunctional nanocarriers not only boosted the apoptosis of cervical cancer cells compared with free cisplatin but also dramatically decreased the production of Kyn to simultaneously potentiate effector T cell differentiation in the tumor microenvironment. These data are in accordance with reported findings …”
Section: Delivery System For Provoking Antitumor Immunitysupporting
confidence: 94%
“…These multifunctional nanocarriers not only boosted the apoptosis of cervical cancer cells compared with free cisplatin but also dramatically decreased the production of Kyn to simultaneously potentiate effector T cell differentiation in the tumor microenvironment. These data are in accordance with reported findings …”
Section: Delivery System For Provoking Antitumor Immunitysupporting
confidence: 94%
“…Synthetic micelles have been used to either directly modulate the immune system as a part of a combinatorial approach to reduce tumor burden or as a vaccine nanocarrier against cancer and other ailments. As an immunomodulatory vehicle, several types of synthetic micelles have been developed, including: i) a PEG‐PLGA‐based micelle with collagen IV‐targeting peptides to deliver the anti‐inflammatory peptide (Ac2‐26) to exert tissue‐restorative properties to the vascular basement membrane, ii) a monomethyl PEG–PCL micelle to envelope and deliver fisetin for activating cell surface death receptors in colon tumors, iii) an acid‐activatable cationic micelle encapsulating photosensitizers for combinatorial PDT and siRNA delivery to knockdown PD‐L1 expression, and iv) a PEG‐prodrug (NLG919, an IDO inhibitor) conjugate‐based micelle to reduce tumor‐associated immunosuppression and improve outcomes when combined with systemic paclitaxel . Monomethyl PEG–PCL micelles have also been used to encapsulate NLG919 and photosensitizers for PTT, activating antigen‐specific CTLs and generating abscopal effects …”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…Other than the common application of PD‐1 in combinational therapy, incorporating IDO inhibitors into chemotherapy has also became attractive because of the dramatic boost of conventional cancer chemotherapeutics. Y. C. Chen et al () introduced a co‐delivery system with PTX encapsulated in a nanomicellar carrier grafting the IDO inhibitor of NLG919 (PEG 2k ‐Fmoc‐NLG) as combination therapy. Outcomes in 4T1.2 cancer and B16 melanoma mice models indicated that the co‐delivery of PTX and NLG919 provided stronger antitumor efficiency.…”
Section: Combinational Cancer Immunotherapy With Nanoparticlesmentioning
confidence: 99%